Synthesis and characterization of nano-sized LiFePO4 by using consecutive combination of sol-gel and hydrothermal methods. (20th January 2021) - Alsamet, Mohammed A.M.M.; Burgaz, Engin
Highlights: Nano-sized LiFePO4 was synthesized by merging sol-gel and hydrothermal methods. Both samples have well olivine crystal structure and plate-like morphology. The capacities of HY-SO-LiFePO4 are close to those of HY-LiFePO4 at low C. HY-SO-LiFePO4 displays higher capacities than those of HY-LiFePO4 at high C. Abstract: Lithium iron phosphate (LiFePO4 ) was synthesized by means of a new route which is based on the combination of sol-gel and hydrothermal methods (HY-SO-LiFePO4 ). The results of HY-SO-LiFePO4 were compared with those of LiFePO4 which was synthesized by using only hydrothermal method (HY-LiFePO4 ). The crystalline structure and morphology of LiFePO4 nanoparticles were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Based on XRD data, LiFePO4 powders have a well olivine crystal structure with a space group of Pnma. The slight decrease of crystalline lattice parameters in HY-SO-LiFePO4 was observed compared to that of HY-LiFePO4 . LiFePO4 powders have homogeneous distribution of nanoparticles with a plate-like morphology. Also, the plate length decreases from 300-500 nm to 150–350 nm if sol-gel and hydrothermal methods are consecutively used together. The as-prepared LiFePO4 coin cells were characterized via cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), and their charge/discharge experiments were performed at different current rates in a range of 2.5-4.2V vs. Li/Li + . The discharge capacities of HY-SO-LiFePO4 were found as 126 mAhg −1 at 0.2C and 70 mAhg −1 at 3C. Meanwhile, HY-SO-LiFePO4 cathode exhibits a stable charge/discharge cycle ability (>97.5% capacity retention after 100 charge/discharge cycles compared with HY-LiFePO4 cathode which is 77.7% at 0.5C). The overall experimental results revealed the idea that positioning the wet gel inside reactor may impede the growth of grains and lead to the formation of smaller LiFePO4 nanoparticles with a narrow size distribution during reactive synthesis procedure. Hence, these results improve the electrochemical performance of cathode material. Graphical abstract: Image, graphical abstract